PARANEOPLASTIC HYPOGLYCEMIA IN HEPATOCELLULAR CARCINOMA: A REPORT OF TWO CASES - Shing, Wong Pei; Aziz, Hazwani; Katiman, Elliyyin (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hepatocellular carcinoma (HCC) is the second most common cause of non-islet cell tumor hypoglycemia (NICTH), with a reported prevalence varying from 4% to 27%. It can also be an early presentation of HCC, even before the tumour is large enough to be detected on imaging. We report two cases of NICTH in patients with viral hepatitis-associated HCC. CASE Case 1: A 64-year-old male presented with severe hypoglycemia (glucose 1.8 mmol/L) during an admission for spontaneous bacterial peritonitis. He was newly diagnosed with Child-Pugh C liver disease from chronic hepatitis C. Hypoglycemia persisted despite resolution of sepsis, requiring continuous dextrose 50% infusion. Physical examination revealed a hard mass in the right upper quadrant. Laboratory findings included elevated AFP at >830 IU/mL, low albumin at 24 g/L, INR of 1.5, bilirubin of 25 µmol/L, and platelet count of 180 x10⁹/L. CT imaging showed a cirrhotic liver with a segment II mass (4.2 x 4.0 x 4.0 cm). Laboratories done during hypoglycemia showed low levels of insulin at <0.5 mIU/L (normal 3–25), low C-peptide at 46 pmol/L (298–2350), low IGF-1 at 10.5 ng/mL (42–179), and HbA1c of <3.4% (Hb 9.6 g/dL). IGF-2 testing was unavailable. Case 2: A 48-year-old female with chronic hepatitis B and a large HCC (14 x 10 x 9 cm) and elevated AFP at 8,925 IU/mL. She presented with symptomatic hypoglycemia (glucose 2.5 mmol/L). Prolonged fasting revealed hypoglycemia at 4 hours (glucose 2.1 mmol/L), with insulin of <2 µIU/mL, C-peptide of <33 pmol/L, IGF-1 of 17 ng/mL (normal 90–249), and cortisol at 509 nmol/L. The presence of inappropriately low insulin and low c-peptide during an episode of hypoglycemia favors the diagnosis of NICTH. Both cases were managed with oral prednisolone 1 mg/kg which allowed for successful weaning from dextrose. Despite transient stabilization, both patients succumbed within one month. CONCLUSION Paraneoplastic hypoglycemia should be considered in HCC patients with unexplained hypoglycemia. Early recognition and glucocorticoid therapy may improve short-term outcomes, though prognosis remains poor.